The object of the assessment – part of the teachers’ evaluation - DRAGOMIR, Robert Gabriel; TASCOVICI, Daliana Ecaterina (Annals of Spiru Haret University. Economic Series, 2010)
The present paper is part of an ample research on a teacher assessment model in the pre university education system. The purpose was to establish the theoretical aspects of the assessment object taken into consideration. Thus, I have presented and described the assessment object, which involves the teacher’s performance, the content and the result of the teacher’s activity, which is materialized in the pupil’s knowledge.